Pelatihan Penggunaan Fitur Mail Merge Dalam Microsoft Office Untuk Surat Menyurat Bagi Aparat Desa Mekar Jaya, Kabupaten Tangerang - Endrawijaya, Ika; Ismail, KGS. M.; Supri, Supri; Anam, Khoirul; Himayati, Arini Zulfa; Wildan, Muh.; Adiliawijaya, Rany (Politeknik Penerbangan Indonesia Curug, 2024)
The development of information technology plays a very important role in supporting work in all fields, including village government. Industrial technology has been applied in almost all village governments, to support the performance of the Village Head, Village Consultative Body and Village Apparatus/Apparatus. One of the software that can be used to support administrative activities is Microsoft Office which consists of Microsoft Word, Excel and Power Point. Microsoft Office software has many features, including the mail merge feature, but most of the features are still unfamiliar to use by Mekar Jaya village officials, Panongan District, Tangerang Regency, Banten, because they are still not used to using the tools available in Microsoft Office. Therefore, the Community Service team provided training on the use of the mail merge feature in Microsoft Office for correspondence for 20 Mekar Jaya village officials, Panongan District, Tangerang Regency, to increase the knowledge and skills of training participants regarding the use of the mail merge feature in Microsoft Office through lecture and discussion methods. and direct practice using a personal computer for each participant, guided by a team of competent lecturers and instructors. Based on the evaluation results, it show that after attending the training, the participants understood the material provided and were able to use the mail merge feature in making invitations, certificates, and correspondence. Participants' ability to use and utilize the mail merge feature is very necessary to improve their performance.